PEMASANGAN TIANG PENYANGGA PANEL SURYA PADA GEREJA OLLON - Limbran Sampebatu (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Poles are one of the important equipment in the construction of a PLTS. The pole is the main support for the solar panel which must be positioned so that the solar panel can be exposed to sunlight in a perfect position. This support pole can be made of wood or of iron / steel. The requirements for a support pole used to support solar panels are to have high mechanical strength, have a long life, easy to install and cheap to maintain, not too heavy, low price, attractive appearance, easy to remove and reinstall. Wooden poles are widely used as a support for solar panels because of their simple construction and lower investment costs. However, the weakness of this wooden pole is that it is very dependent on the existing wood supply, needs preservation first, shorter service life, and cannot safely support the load. Steel poles are widely used because of their sturdier construction, straighter and more beautiful shape than wooden poles. However, considering the location of the service which is quite difficult to reach by vehicle, it hinders the transportation of iron/steel poles to the service location. So that the pole used as a support pole is a wooden pole that has been preserved first